การจัดการความรู้ในการสร้างตำบลน่าอยู่ของเทศบาลตำบลอุโมงค์ อำเภอเมือง จังหวัดลำพูน - รุ่งอรุณ อินทร์มณี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The study of Knowledge Management in Creating Healthy Community of U-Mong Subdistrict Municipality, Mueang District, Lamphun Province aimed to study the process of knowledge management that led to the development of a prototype livable community, including factors related to the success in driving the policy of livable community, and to present the results of the livable community due to the development in economy, society, culture, and environment. The research methodology was a qualitative research by using the case study. Data used in this study was from the interview with 22 informants or 3 groups of people as follows: (1) eleven community leaders included Subdistrict Chief and Village Headman (2) ten representatives of learning resources (3) one executive of U-Mong Subdistrict Municipality included the mayor or the deputy mayor. Furthermore, there were studying of the relevant academic documents. The results of the study were shown as below. Knowledge management of U-Mong Subdistrict Community was consistent with TUNA Model which was linked to the development goal of the district, the development vision, the strategic development plan, and the community plan. There were various individuals involved in knowledge management of U-Mong Subdistrict such many as local executives, community leaders, the commissions who were appointed by U-Mong Subdistrict Municipality, network members who were from both inside and outside community, members of 24 learning resources, team learning lecturer, and U-Mong Subdistrict Municipality. Besides, the four factors of the entire community included community infrastructure, communication, participation, human development in community were the driving force for the community to be strengthened significantly. The results of operations in development had appeared in form of management and changes in economy, society, culture, and environment. The suggestions of the study were as follows: (1) many groups in community should be supported and strengthened capacity to be the new learning resources for U-Mong Subdistrict Community and to be the model for other communities in education (2) there should be the indicators to assess the implementation of learning resources in each place in U-Mong Subdistrict Community to get the information as a guideline for potential analysis to determine the way to develop the learning resources (3) the participation of the public in attending activities or learning resources of U-Mong Subdistrict Community was limited to only certain parts, so U-Mong Subdistrict Municipality should organize activities or projects to create more opportunities for the access of public sector and community leaders.